2013
DOI: 10.1111/1755-0998.12175
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of 11 single‐locus and seven multilocusDNAbarcodes inLamiumL. (Lamiaceae)

Abstract: The aim of this work was to evaluate the suitability of selected DNA regions in the barcoding of plants, based on the species belonging to the genus Lamium (Lamiaceae). For this purpose, nine chloroplast barcodes, that is, accD, matK, rbcL, rpoA, rpoB, rpoC1, rpoC2, trnH-psbA, trnL-trnF, as well as ITS nuclear region, and intron of mitochondrial nad5 gene were tested. Among the single-locus barcodes, most effective in the identification of Lamium species was the trnH-psbA spacer and matK gene. The high level o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
39
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(44 citation statements)
references
References 55 publications
(161 reference statements)
4
39
0
1
Order By: Relevance
“…laevigatum a separate taxon. This result is consistent with the analysis of variation of barcoding sequences in the genus Lamium, which also indicated the distinctiveness of this subspecies (Krawczyk et al 2014;.…”
Section: Diagnostic Features Of Species Of Hybrid Originsupporting
confidence: 90%
See 1 more Smart Citation
“…laevigatum a separate taxon. This result is consistent with the analysis of variation of barcoding sequences in the genus Lamium, which also indicated the distinctiveness of this subspecies (Krawczyk et al 2014;.…”
Section: Diagnostic Features Of Species Of Hybrid Originsupporting
confidence: 90%
“…The results of phylogenetic studies showed that L. galeobdolon did not form a separate phylogenetic line in relation to the genus Lamium and thereby confirmed that the presence of L. galeobdolon in Lamium was justified . Molecular studies confirmed a close relationship of L. flexuosum, L. galeobdolon and L. orvala (Krawczyk et al 2014). The infrageneric classification based on macromorphological features also emphasizes the similarity of L. galeobdolon and L. flexuosum which constitute the subgenus Galeobdolon, while L. orvala belongs to the monospecific subgenus Orvala (Mennema 1989).…”
Section: Diagnostic Features Of Species Of Hybrid Originmentioning
confidence: 64%
“…Recently, several candidate DNA regions, such as the internal transcribed spacer 2 (ITS2), megakaryocyte-associated tyrosine kinase (matK), a large subunit of the ribulose-1,4-bisphosphate carboxylase gene (rbcL), and the intergenic spacer photosystem II protein D1-tRNA-His (psbA-trnH), or a combination of them have been popularly used as suitable DNA barcodes in plants. [18][19][20][21] Lahaye et al recommended matK as a universal DNA barcode for flowering plants. 17) The Plant Working Group of the Consortium for the Barcode of Life (CBOL) officially proposed that rbcL and matK were able to serve as core barcodes, and psbA-trnH or ITS regions could serve as supplemental loci for differentiating plant species.…”
mentioning
confidence: 99%
“…Mean pairwise identity for coding regions was 96.6%. The nucleotide variation in the gene coding Acetyl-CoA carboxylase (accD) is not surprising, since it has proven its usefulness many times in plant barcoding studies (Newmaster et al, 2008;Krawczyk et al, 2014). In coding regions, the total number of nonsynonymous and synonymous mutations was similar at 354 and 375, respectively ( Figure 5).…”
Section: Comparative Genomicsmentioning
confidence: 99%